Methicillin-resistant Staphylococcus aureus bloodstream infection: risk factors and clinical outcome in non-intensive-care units - Karinne Spirandelli Carvalho Naves; Natália Vaz da Trindade; Paulo Pinto Gontijo Filho (Revista da Sociedade Brasileira de Medicina Tropical, 2012)
INTRODUCTION: Methicillin-resistant Staphylococcus aureus (MRSA) is spread out in hospitals across different regions of the world and is regarded as the major agent of nosocomial infections, causing infections such as skin and soft tissue pneumonia and sepsis. The aim of this study was to identify risk factors for methicillin-resistance in Staphylococcus aureus bloodstream infection (BSI) and the predictive factors for death. METHODS: A retrospective cohort of fifty-one patients presenting bacteraemia due to S. aureus between September 2006 and September 2008 was analysed. Staphylococcu aureus samples were obtained from blood cultures performed by clinical hospital microbiology laboratory from the Uberlândia Federal University. Methicillinresistance was determined by growth on oxacillin screen agar and antimicrobial susceptibility by means of the disk diffusion method. RESULTS: We found similar numbers of MRSA (56.8%) and methicillin-susceptible Staphylococcus aureus (MSSA) (43.2%) infections, and the overall hospital mortality ratio was 47%, predominantly in MRSA group (70.8% vs. 29.2%) (p=0.05). Age (p=0.02) was significantly higher in MRSA patients as also was the use of central venous catheter (p=0.02). The use of two or more antimicrobial agents (p=0.03) and the length of hospital stay prior to bacteraemia superior to seven days (p=0.006) were associated with mortality. High odds ratio value was observed in cardiopathy as comorbidity. CONCLUSIONS: Despite several risk factors associated with MRSA and MSSA infection, the use of two or more antimicrobial agents was the unique independent variable associated with mortality.